Community engagement, greening, and violent crime: A test of the greening hypothesis and Busy Streets. Issue 1 (10th October 2022) - Gong, Catherine H.; Bushman, Gregory; Hohl, Bernadette C.; Kondo, Michelle C.; Carter, Patrick M.; Cunningham, Rebecca M.; Rupp, Laney A.; Grodzinski, Alison; Branas, Charles C.; Vagi, Kevin J.; Zimmerman, Marc A.
Abstract: Researchers have documented that vacant lot greening can reduce community‐level crime and violence. Busy Streets Theory (BST) suggests that residents who are involved in the greening process can help to improve physical environments and build social connections that deter crime and violence. Yet few researchers have explored how community engagement in the greening process may affect crime and violence outcomes. We applied BST to test the effects of community‐engaged vacant lot greening compared to vacant lots that received either professional mowing or no treatment, on the density of violent crime around study lots. Using mixed effects regression models, we analyzed trends in violent crime density over the summer months from 2016 to 2018 at 2102 street segments in Youngstown, OH. These street segments fell within 150 meters of an intervention parcel that was classified as one of three conditions: community‐engaged maintenance, professional mowing, or no treatment (control). We found that street segments in areas receiving community‐engaged maintenance or professional mowing experienced greater declines in violent crime density than street segments in areas receiving no treatment, and more decline occurred in the community‐engaged condition compared to the professional mow condition. Our findings support BST and suggest that community‐engaged greening of vacant lots in postindustrial cities with a concentrated vacancy can reduce crime and violence. Highlights: Greening of vacant lots is associated with decreases in violent crime. Community‐engaged greening is associated with a greater decrease in crime than professional mowing. Community‐engaged greening of vacant lots in cities can reduce violence.